2022
DOI: 10.1002/csr.2352
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and export performance under stakeholder view: The mediation of innovation and the moderation of the legal form

Abstract: Prior confronting findings on the association between corporate social responsibility and profitability show that some aspects remain to be clarified about this binomial.Contributing to this body of research is particularly interesting in the case of the exporters to understand the role that corporate social responsibility may play in improving export performance. This study aims to determine the impact of firms' corporate social responsibility efforts on their export performance by examining innovation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 103 publications
3
19
0
Order By: Relevance
“…Accordingly, the extant research has explored the effects and outcomes of social responsibility in different businesses (Chuah et al, 2020; Farrington et al, 2017; Kim, Rhou, et al, 2017; Su et al, 2017; Su & Swanson, 2019; Theodoulidis et al, 2017; Youn et al, 2018). However, most of these studies examine the effects of CSR on firm financial performance (Khavarinezhad et al, 2022; Kim, Rhou, et al, 2017; Lee et al, 2018; Theodoulidis et al, 2017); customer loyalty (Chuah et al, 2020; Kim et al, 2013; Xu, 2014); innovation (Martos‐Pedrero et al, 2022); and customer behavioural intent (Lichtenstein et al, 2004; Martínez & Rodríguez del Bosque, 2013; Sen et al, 2006). Therefore, many researchers have suggested that more attention should be paid to the potential positive effects of CSR actions (Chuah et al, 2020; Farrington et al, 2017; Sabokro et al, 2021; Su et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the extant research has explored the effects and outcomes of social responsibility in different businesses (Chuah et al, 2020; Farrington et al, 2017; Kim, Rhou, et al, 2017; Su et al, 2017; Su & Swanson, 2019; Theodoulidis et al, 2017; Youn et al, 2018). However, most of these studies examine the effects of CSR on firm financial performance (Khavarinezhad et al, 2022; Kim, Rhou, et al, 2017; Lee et al, 2018; Theodoulidis et al, 2017); customer loyalty (Chuah et al, 2020; Kim et al, 2013; Xu, 2014); innovation (Martos‐Pedrero et al, 2022); and customer behavioural intent (Lichtenstein et al, 2004; Martínez & Rodríguez del Bosque, 2013; Sen et al, 2006). Therefore, many researchers have suggested that more attention should be paid to the potential positive effects of CSR actions (Chuah et al, 2020; Farrington et al, 2017; Sabokro et al, 2021; Su et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The application of the incentive system mitigated the partial rise in production costs (Figure 4b). The use of subsidized photovoltaic energy resulted in a partial decrease in production costs of 6.0%, which could be amplified by the increase in energy prices due to the political instability in Eastern Europe and the Honoré et al, 2019;Martos-Pedrero et al, 2022) and in other sectors, such as energy (Balcilar et al, 2022).…”
Section: Statistical Treatmentmentioning
confidence: 99%
“…Some are currently in the experimental phase (MAPA & Cajamar, 2022). The implementation of eco-innovations depends fundamentally on the process, organizational and marketing dimensions T A B L E 1 Top 10 EU member states in fruit and vegetable production (including melons and strawberries) in 2020. of companies in the agri-food sector (García-Granero et al, 2020;Martos-Pedrero et al, 2022).…”
Section: Sustainable Development To Avoid Damaging the Environmentmentioning
confidence: 99%
“…For example, Charoensukmongkol (2020) considered the managerial satisfaction from export activities to measure EP. To be more comprehensive, some of the studies considered both objective measures to evaluate EP (Martos-Pedrero et al , 2022; Ngo-Thi-Ngoc and Nguyen-Viet, 2021). For example, Ngo-Thi-Ngoc and Nguyen-Viet (2021) considered sales growth; meeting expectations, export profitability and export market share to measure EP.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For example, Ngo-Thi-Ngoc and Nguyen-Viet (2021) considered sales growth; meeting expectations, export profitability and export market share to measure EP. Martos-Pedrero et al (2022) also evaluated EP by considering the achievement of export objectives including sales, profitability, and market share; the export intensity (the percentage exports represent over total sales); and the extent of satisfaction of the managers with the outcome of its export activity. Accordingly, the current study also counts both subjective and objective measures to evaluate EP considering two variables of sales growth and manager satisfaction with export as suggested by Navarro-García et al (2015).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%